EXHUMATION OF MESSINIAN EVAPORITES IN THE DEEP-SEA AND CREATION OF DEEP ANOXIC BRINE-FILLED COLLAPSED BASINS - Cita M.B. (My University, 2006)
The first part of the paper summarizes some basic concepts concerning (a) the distribution of Messinian evaporites in the deepest parts of the Mediterranean Sea and (b) the Mediterranean Ridge accretionary wedge and its peculiar characteristics deriving from the presence of a substantial evaporitic body in the deforming sedimentary prism. Then five brine-filled anoxic collapsed basins (Tyro, Bannock, Urania, Atalante and Discovery), discovered from 1983 to 1994, are presented and discussed in their physiographic, geologic, hydrologic and geochemical characters. High density brines deriving from submarine dissolution of outcropping or subcropping evaporites accumulate at the bottom of collapsed basins, if they are not swept away by submarine currents. The interface separating normal sea-water from high density brines is sharp with a density contrast of about 20% and lies at 3200-3500 m below sea level. Strong bacterial activity is developing at the interface and living bacteria have been recovered from the anoxic salty brines. Thickness of the brines may be up to 500 m. Thermal stratification has been observed in three brine lakes. Exhumation and dissolution of Messinian evaporites in the Mediterranean Ridge occur in different tectonic settings: pull-apart basin (Tyro), subducting seamount close to the outer deformation front (Bannock Basin), top of a backstop (Urania, Atalante and Discovery Basins). Chemistry of the brines is strongly variable and suggests dissolution of different layers or levels of the Messinian suite. Discovery brines are the saltiest ever recorded in natural environment. Their saturation in Mg chloride (bischofite), the end product of sea-water evaporation, suggests that the deepest parts of the eastern Mediterranean were close to dryness at the end of the salinity crisis, strongly supporting the deep basin desiccation model. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANOXIC BRINE LAKES; EXHUMATION; MESSINIAN EVAPORITES; Messinian; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский